Primary intraosseous Rosai–Dorfman disease: An analysis of clinicopathologic characteristics, molecular genetics, and prognostic features - Weng, Xin; Yang, Yajie; Zhang, Meng; Cai, Chang; Sun, Yanhua; Wu, Xikang; Zhang, Rongrong; Gui, Huihui; Li, Wei; Xu, Qizhong; Liu, Xia (Frontiers in Oncology, 2022)
Background Rosai–Dorfman disease (RDD) is a rare histiocytic proliferative disorder of uncertain pathogenesis. Most patients present with proliferation in the lymph nodes manifesting as adenopathy; however, RDD may primarily arise in a variety of extranodal sites, including the bone, which is a great challenge in the diagnosis. The clinicopathological characteristics and prognostic features of primary intraosseous RDD have not been well characterized. Methods We retrospectively analyzed the clinicopathologic and prognostic features of four cases of primary intraosseous RDD during the past 10 years in our hospital, with a review of an additional 62 cases with complete follow-up data from the literature. Results Primary intraosseous RDD was identified in 0.14% (4/2,800) of total bone biopsies performed at our institution over the study period. According to our retrospective analysis, a total of 18 cases of primary lymph node, skin, or other non-osseous site-based RDD were diagnosed in our hospital. The ages of the 66 total patients ranged from 1.5 to 76 years, with a median age of 25 years. There were 31 male and 35 female patients, with a male-to-female ratio of 0.89:1. Primary intraosseous RDD occurred most often in the bones of the extremities (60.6%, 40/66), with the proximal tibia being the most common location; 39.4% (26/66) of the cases arose in the axial skeleton, predominantly in the vertebra and craniofacial bones. Solitary masses and multiple tumors were present in 84.8% (56/66) and 15.2% (10/66) of the cases, respectively. Pain of the affected area was the most common presenting symptom. Radiographically, the lesions were lytic with well-defined and usually sclerotic margins. Immunohistochemistry showed that large histiocytes from patients with RDD were positive for OCT2, in addition to S100 and CD68. Molecular tests were performed in seven reported cases and four of our cases. All the 11 cases were non-decalcified. PCR results showed that there were no BRAF-V600E, KRAS, or NRAS mutations in primary intraosseous RDD; only one case with both RDD and Langerhans cell histiocytosis showed BRAF-V600E mutation. The survival data showed that 22.7% (15/66) of the patients experienced recurrences or developed RDD at distant sites during the follow-up period (median follow-up, 13 months; range, 1–106 months). The 5-year progression-free survival (PFS) of the patients with primary intraosseous RDD was 57.5%. We found that there was a significant difference in PFS between female and male patients (p = 0.031). However, there was no statistically significant difference in PFS between patients with solitary masses and multiple tumors (p = 0.698). Similarly, no statistically significant differences in PFS were found between the different age groups (p = 0.908) or tumor locations (p = 0.728). Conclusion Primary intraosseous RDD is an extremely rare disease. The diagnosis of RDD may be quite challenging because of its non-specific clinical presentation and imaging. Immunohistochemistry showed that large histiocytes were positive for OCT2 in addition to S100 and CD68, which may be helpful for differential diagnosis. Molecular detection showed that RDD may be related to the MAPK pathway, though these results are also ultimately not specific. The pathogenesis of RDD is yet to be elucidated, but recent studies suggest possible clonality of hyperproliferative histiocytes.